Promoting SPELL ELC Using a Marketing Booklet - Arniescza Utomo (Institute of Research and Community Outreach - Petra Christian University, 2019)
SPELL ELC (Special Programs for English Language & Literacy English Language & Communication) is an English institution located in Pondok Mutiara blok MEA 8, Sidoarjo. This company claims themselves as an English school. It provides three kinds of English education programs which are English for Children’s Programs, English for Academic Programs, and English for Business Programs. Those programs focus on the kids to adults students based on their needs. However, there are only few people know these programs. It means that they need to be promoted in order to make this institution well-known by others. Therefore, creating a marketing booklet is the best solution for SPELL ELC since the booklet provides complete information about each programs to the potential customers. The content of marketing booklet consists of company’s overview, products’ description, and contact information. In the products description, the information is more emphasized so that the customer can read them clearly. Key words: promotion tool, marketing strategy, marketing booklet